2016
DOI: 10.1017/s0007114515000768
|View full text |Cite
|
Sign up to set email alerts
|

Mental performance in 8-year-old children fed reduced protein content formula during the 1st year of life: safety analysis of a randomised clinical trial

Abstract: In humans, maximum brain development occurs between the third trimester of gestation and 2 years of life. Nutrition during these critical windows of rapid brain development might be essential for later cognitive functioning and behaviour. In the last few years, trends on protein recommendations during infancy and childhood have tended to be lower than that in the past. It remains to be demonstrated that lower protein intakes among healthy infants, a part of being able to reduce obesity risk, is safe in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The EU CHOP studied the effect of variations in protein supply within the normal ranges on the brain development of healthy infants during the first year of life. Children (eight years of age) were subjected to a comprehensive battery of neuropsychological tests, including several measures of memory, attention, and executive functions, 48 but the results of these tests did not differ between children fed high- and low-protein formulas.…”
Section: Can Protein Intake In Infancy Affect Other Tissues?mentioning
confidence: 99%
See 1 more Smart Citation
“…The EU CHOP studied the effect of variations in protein supply within the normal ranges on the brain development of healthy infants during the first year of life. Children (eight years of age) were subjected to a comprehensive battery of neuropsychological tests, including several measures of memory, attention, and executive functions, 48 but the results of these tests did not differ between children fed high- and low-protein formulas.…”
Section: Can Protein Intake In Infancy Affect Other Tissues?mentioning
confidence: 99%
“…The minimum levels of 1.8 g/100 kcal in infant formulas and 2.2 g/100 kcal in follow-on formulas from the EU CHOP study were shown to be safe in terms of longitudinal growth 20 and long-term neurodevelopment. 48 However, considering the protein supply in human milk, which is being reduced during the first year of life, these minimum ranges may still exceed nutritional needs starting at age three months. 70 In a recently published study, Ziegler et al showed that an infant formula containing protein levels below the regulatory lower limit (1.61 g protein/dl) and a formula with a higher protein content provided similar longitudinal growth rates.…”
Section: Changes In the Recommended Protein Contents In Infant And Fomentioning
confidence: 99%
“…In the current study, we aimed to demonstrate the long-term effects of early nutrition on brain structure and its consequences on neurodevelopment. To achieve this aim, cognitive function was evaluated using wide range of valid, reliable, and age-appropriate tests focused on diverse child brain domains ( 43 , 44 ) in contrast with other studies based on evaluation of a single brain domain. Interestingly, our nutritional intervention was performed from 0 to 2 months and prolonged up to 18 months of life, which yields results with added value with respect to other studies with a shorter time of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Computerized Battery for Neuropsychological Evaluation of Children (BENCI) is a computerized tool that evaluates neuropsychological functions and neurodevelopmental domains in children, such as immediate and delayed memory, attention, visual motor coordination, verbal fluency and comprehension, processing speed, and executive functions ( 31 , 43 ). All these tests were developed using valid neuropsychological procedures assumed from the literature of neuropsychological assessment, and were principally based on the NUTRIMENTHE Neuropsychological Battery ( 43 , 44 ). In the current study, neurocognitive function was assessed using the following tasks ( 45 ):…”
Section: Methodsmentioning
confidence: 99%
“…Children´s neurocognitive development was assessed using a NUTRIMENTHE neuropsychological battery (NNB), a comprehensive neuropsychological battery specifically developed for the NUTRIMENTHE project [19,27,28]. For the present study, NNB was used to evaluate long-term effects of prenatal supplementation on the whole spectrum of neuropsychological functioning in children.…”
Section: Neuropsychological Assessment (Secondary Outcome)mentioning
confidence: 99%